2020
DOI: 10.1186/s12955-019-1265-z
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in children with infrequent congenital heart defects: cohort study with one-year of follow-up

Abstract: Background: The evidence regarding patient related outcomes in children with infrequent congenital heart defects (I-CHD) is very limited. We sought to measure quality of life (QoL) in children with I-CHD, and secondarily, to describe QoL changes after one-year of follow-up, self-reported by children and through their caregivers' perspective. Methods: We assembled a cohort of children diagnosed with an I-CHD in a cardiovascular referral center in Colombia, between August 2016 and September 2018. At baseline and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…In the cardiac-specific module, "cognitive status" showed the lowest scores in the evaluation both at baseline and follow-up. 27 Therefore, this shows that although children perceive their quality of life to be better than their caregivers, the overall quality of life of children with CHD was generally lower than that of a healthy child. This is also in line with a study carried out by Katelyn Mellion et al, which stated that children with CHD had a significantly lower score on QoL assessment compared to that of healthy controls.…”
Section: Quality Of Life Of Patients With Vsdmentioning
confidence: 89%
See 2 more Smart Citations
“…In the cardiac-specific module, "cognitive status" showed the lowest scores in the evaluation both at baseline and follow-up. 27 Therefore, this shows that although children perceive their quality of life to be better than their caregivers, the overall quality of life of children with CHD was generally lower than that of a healthy child. This is also in line with a study carried out by Katelyn Mellion et al, which stated that children with CHD had a significantly lower score on QoL assessment compared to that of healthy controls.…”
Section: Quality Of Life Of Patients With Vsdmentioning
confidence: 89%
“…In this study, 157 children with CHD underwent quality of life (QoL) assessment with 112/157 (71%) achieving 1-year follow-up. 27 The PedsQL 4.0 scale, which included generic and cardiac-specific modules was used for QoL evaluation. 27 Results from both modules showed that the children with CHD showed a better perception in the QoL evaluation compared to their caregivers who showed a less prominent perception of their children's QoL.…”
Section: Quality Of Life Of Patients With Vsdmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have been conducted on postoperative QOL of patients with CHD, but results are inconsistent. Patients with CHD score similar to or better than their healthy peers in QOL questionnaires [26][27][28], but some studies argue that QOL might be compromised [15,29] The disagreement may have arisen from heterogeneity in subject demographics, the questionnaire used, specific CHD, or country of origin. Our study is the first to focus on the impact of different surgical methods on CHD repair.…”
Section: Discussionmentioning
confidence: 99%
“…The HRQoL responses for children aged 8–18 years and their parents were scored on a 5-item Likert scale: 0 for never, 1 for almost never, 2 for sometimes, 3 for often, and 4 for always. 18 , 19) Scores ranged from 0 to 100 points. The total score for each dimension was calculated as the sum of the scores for all questions in that dimension divided by the number of questions for that dimension.…”
Section: Methodsmentioning
confidence: 99%